Productivity and quality of Moina sp. cultivated with various culture medium - Taufik Shidik Adi Nugroho Shidik; Julie Ekasari; Dedi Jusadi; Mia Setiawati (Jurnal Akuakultur Indonesia)
Cultivation of Moina sp is still constrained by its quality, productivity, and sustainability. The alternative solution is the use of cultivation media materials that have high nutritional content and easily available in large quantities to support the quality and productivity of Moina sp. and meet the needs of live feed. The objective of the study was to evaluate the effect of various culture medium on the productivity and nutritional quality of Moina sp.. Five culture media were tested in laboratory scale, i.e. organic ingredient (BO), Chlorella sp. (Ch), Chlorella sp. + organic ingredients (ChBO), biofloc (BF) and biofloc + organic ingredients (BFBO). While in mass scale, four culture media were tested, i.e. Chlorella sp. (Ch), Chlorella sp. + Organic Ingredients (ChBO), Biofloc (BF) and Biofloc + Organic Ingredients (BFBO). The peaks of Moina sp. density in different treatments were achieved in different days. ChBO treatments significantly had higher productivity (P<0.05). The highest protein content was found in Moina sp. cultured with ChBO media, even higher than artemia. Moina sp. cultured with Chlorella sp. (Ch) showed the highest PUFA (Poly Unsaturated Fatty Acids) contents, while the highest MUFA (mono unsaturated fatty acids) contents was obtained from Moina sp. cultured with BFBO media lower than artemia. The study results indicates that different culture media produces different productivity and nutrient quality of Moina sp. The organic material combination of Chlorella sp. + organic material (ChBO) was the best media to improve the productivity and protein quality of Moina sp.